A review of the stink bug genus Plautia Stål from Japan (Hemiptera, Heteroptera, Pentatomidae) - Ishikawa, Tadashi; Moriya, Seiichi (Zootaxa, 2019)
In this review, we revise the pentatomine stink bug genus Plautia Stål from Japan. Five species are recognized and diagnosed, including three new species: P. sakishimensis sp. nov., P. himechabane sp. nov., and P. ishigaki sp. nov. One of these, P. himechabane sp. nov., was previously regarded as P. splendens Distant for the populations of the mainland of Japan, the Ryukyu Islands, and China. The species Plautia cyanoviridis Ruckes is proposed as a junior synonym of P. splendens, which is endemic to the Ogasawara Islands. A key is provided to facilitate the identification of the five species known in Japan.